Onset Patterns and Course of Myalgic Encephalomyelitis/Chronic Fatigue Syndrome - Chu, Lily; Valencia, Ian J.; Garvert, Donn W.; Montoya, Jose G. (Frontiers in Pediatrics, 2019)
Background: Epidemiologic studies of myalgic encephalomyelitis/ chronic fatigue syndrome (ME/CFS) have examined different aspects of this disease separately but few have explored them together. Objective: Describe ME/CFS onset and course in one United States-based cohort. Methods: 150 subjects fitting Fukuda 1994 CFS criteria completed a detailed survey concerning the initial and subsequent stages of their illness. Descriptive statistics, graphs, and tables were used to illustrate prevalence and patterns of characteristics. Results: The most common peri-onset events reported by subjects were infection-related episodes (64%), stressful incidents (39%), and exposure to environmental toxins (20%). For 38% of subjects, more than 6 months elapsed from experiencing any initial symptom to developing the set of symptoms comprising their ME/CFS. Over time, the 12 most common symptoms persisted but declined in prevalence, with fatigue, unrefreshing sleep, exertion-related sickness, and flu-like symptoms declining the most (by 20%-25%). Conversely, cognitive symptoms changed the least in prevalence, rising in symptom ranking. Pregnancy, menopause, and menstrual cycles exacerbated many women’s symptoms. Fatigue-related function was not associated with duration of illness or age; during the worst periods of their illness, 48% of subjects could not engage in any productive activity. At the time of survey, 47% were unable to work and only 4% felt their condition was improving steadily with the majority (59%) describing a fluctuating course. Ninety-seven percent suffered from at least one other illness: anxiety (48%), depression (43%), fibromyalgia (39%), irritable bowel syndrome (38%), and migraine headaches (37%) were the most diagnosed conditions. Thirteen percent came from families where at least one other first-degree relative was also afflicted, rising to 27% when chronic fatigue of unclear etiology was included. Conclusions: This paper offers a broad epidemiologic overview of one ME/CFS cohort in the United States. While most of our findings are consistent with prior studies, we highlight underexamined aspects of this condition (e.g. the evolution of symptoms) and propose new interpretations of findings. Studying these aspects can offer insight and solutions to the diagnosis, etiology, pathophysiology, and treatment of this condition.